“That's like therapy”—A qualitative study on socially disadvantaged women's views on the effects of a community-based participatory research project on their health and health behavior - Kreiml, Verena; Sauter, Alexandra; Abu-Omar, Karim; Eickmann, Sascha; Herrmann-Johns, Anne (Frontiers in Public Health, 2024)
Background: Regular physical activity has positive effects on both physical and mental health. Nevertheless, socially disadvantaged women are often insufficiently physically active. Through needs-based physical activity offers, community-based participatory research (CBPR) projects have the potential to reach these women and increase the effectiveness of physical activity interventions by supporting women's empowerment, health, and health behaviors. This study aimed to examine socially disadvantaged women's views on the effects of long-term participation in Bewegung als Investition in Gesundheit (BIG, i.e., movement as an investment in health), a long-standing German CBPR project, on their health and health behavior. Methods: Semi-structured qualitative interviews were conducted with 30 participating women at five BIG sites across Germany between April and August 2022. The interviews were recorded, transcribed verbatim, and analyzed using framework analysis. Results: Women reported that participation in BIG classes contributed to their physical, mental, and social health. For many women, the positive effects on their mental and social wellbeing were most important. In addition to increased fitness and improved physical endurance, many participating women were able to expand their social networks, thus receiving further social support, and improve their self-esteem, self-confidence, and self-efficacy. Furthermore, participation in BIG physical activity classes positively influenced the health awareness of many women helping them to improve their activity level and diet over time. Conclusion: Our results suggest that CBPR projects, such as the BIG project, can increase physical activity among socially disadvantaged groups and contribute to their overall health and wellbeing. CBPR projects could thus be considered a key element of health promotion for this target group. Future interventional research is required to confirm and further explore the effects of CBPR interventions and to examine whether the effects can be replicated in other settings.
CRIS-Team Scopus Importer:2024-02-16
Keywords: community-based participatory research; health behavior; low socioeconomic status; mental health; physical activity; qualitative research; social health; women's health